Infusing Catholicism in Teaching and Writing - Davoli, Joanmarie Ilaria (Pázmány Law Review, 2025)
Catholic law faculty instruct not only the minds of students but also reach their souls. Even during times of crisis, such as the 2020 pandemic, Catholic educators courageously developed solutions to protect the health of students while also nurturing their minds and hearts. This article examines the importance that the Church places on education and research through the guidance offered to Catholic educators by the Gifts of the Holy Spirit received in the Sacrament of Confirmation. By infusing Catholicism in teaching and writing, law faculty share the teachings of Christ with both students and scholars.